PENGGUNAAN PEMARKAH KONJUNGSI DALAM KARANGAN BAHASA INGGRIS - Maria Theresia Priyastuti (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2017)
This research discusses the use of the conjunction markers in the studentsâ€™ English narrative compositions. The aims of the research are to describe the use of the conjunction markers and to explain the mistakes of using the conjunction markers in English composition. The methods of the research are descriptive qualitative and distributional methods. The data were taken from the studentsâ€™ narrative compositions and were analyzed by the researcher using theories of cohesion proposed by Halliday & Hasan (1976). The results of the research are firstly, the use of conjunction markers is â€œand, but, although, when, after, because and soâ€. Secondly some mistakes of using conjunction markers are found in repetition, omission and substition of conjunction markers, in missing of coma punctuation after conjunctions and omission of semantic relations among sentences. Keywords: conjunction, composition, mistakes